Halide Electrolyte Li3InCl6-Based All-Solid-State Lithium Batteries With Slurry-Coated LiNi0.8Co0.1Mn0.1O2 Composite Cathode: Effect of Binders - Wang, Kai; Ye, Qing; Zhang, Jun; Huang, Hui; Gan, Yongping; He, Xinping; Zhang, Wenkui (Frontiers in Materials, 2021)
All-solid-state lithium batteries (ASSLBs) with solid-state electrolytes (SSEs) are considered as a promising next-generation energy storage technology due to their improved safety and higher energy density. Among various SSEs, halide Li3InCl6 is emerging as a promising candidate, because of its high ionic conductivity, air-stability, and wide electrochemical window. Generally, most of the ASSLBs based on inorganic SSEs are assembled by mixed dry pressing, which is not easy to achieve uniform dispersion of powder composite cathode. Here, a slurry coating method by dispersing active materials (LiNi0.8Co0.1Mn0.1O2), SSEs (Li3InCl6), binders (ethyl cellulose, polymethyl methacrylate, styrene butadiene rubber, nitrile rubber) and conductive carbon black in toluene solvent is used to fabricate cathodes. We studied the effects of different kinds of binders and their contents on the electrochemical performance of ASSLBs. The results show that polymethyl methacrylate, ethyl cellulose, styrene butadiene rubber and nitrile rubber binders are all suitable for preparing cathodes, and a binder content of 2 wt% can achieve the best electrochemical performance of the ASSLBs. This work proves that the intimate contact between the active material and the halide SSE in the electrode can be realized by using slurry coating method with suitable binders, thus achieving stable electrochemical performance.